Contribui????es ao ecossistema de dados abertos do Governo Federal com enfoque em tecnologias c??vicas - Freitas, Jos?? Antonio de Carvalho (2016)
Recent advances in transparency of government???s information, coupled with the increasing use of information and communication technologies, have favored the emergence of innovative forms of relationship between society and the government. At the heart of these changes are the open government data, detailing the operation and management of public administration, the use of public resources, public infrastructure and the delivery of public policies to society. Around this rich and potentially useful mass of data and information gravitate various actors, such as their own public institutions, entrepreneurs, civil society organizations, activists engaged in social causes, the media and the citizens themselves. An interconnected set of principles, policies, standards and technologies structure the relationships between these actors, forming a kind of ecosystem that still lacks maturity and is still seeking models for value creation and induction of social progress and sustainability. A path that begins to take shape in this quest is the development of technologies said "civic" which purport to deliver services and information to citizens through high penetration platforms in society, such as phones and other mobile devices. This study addresses aspects of this ecosystem of open data within the Federal Government, focusing on the development of civic technologies, seeking to contribute to a diagnosis of its current structure and proposing some points of improvement. For this, an exploratory approach was used with pragmatic bias, which started the mapping and different dimensions and components of this ecosystem, followed by the development and publication of a civic application for mobile devices. The data obtained in this study allowed us to conduct a review of the current stage of this ecosystem, highlighting its low degree of maturity and pointing to the need for several structural improvements and greater involvement of inducing agents in all analyzed dimensions. In particular, we identified some important gaps in the ecosystem, such as the predominance of transparency???s vision as an end in itself, the low number of Open Data Plans published by public institutions, dispersion, heterogeneity and poor quality of available databases, the lack of clarity regarding the use of licensing to the published data, the absence of a repository of existing civic applications and technologies, the lack of interest of potential users by applications and solutions already available, the lack of sustainability of these solutions and the lack of feedback channels to the government of the data produced by users through civic applications. This research ends bringing some helping tips to treat these gaps targeting the data ecosystem enhancement with the aid of civic technologies.